The causal relationship of female infertility and psychiatric disorders in the European population: a bidirectional two-sample Mendelian randomization study - Pengfei Zeng; Hanxiao Zhang; Liyue Lu; Yanting Li; Tong Yu; Jun Zhang; Hang Zhou (BMC, 2024)
Abstract Background Infertility affects many couples globally, causing physical, emotional, and financial burdens. While observational studies suggest a link between psychiatric disorders and female infertility, causal relationships remain uncertain. Mendelian randomization analysis, using genome-wide association studies data, minimizes confounding factors and reverse causation, providing valuable insights into causal associations. Methods We conducted Mendelian randomization analysis to explore the potential causal relationship between female infertility and psychiatric disorders. Genome-wide association studies summary data for female infertility (112,105 individuals of European ancestry, comprising 11,442 cases and 100,663 controls), depression (807,553 individuals of European ancestry, comprising 246,363 cases and 561,190 controls), anxiety (21,763 individuals of European ancestry, comprising 7,016 cases and 14,745 controls), bipolar disorder (51,710 individuals of European ancestry, comprising 20,352 cases and 31,358 controls), and eating disorders (72,517 individuals of European ancestry, comprising 16,992 cases and 55,525 controls) were utilized. Instrumental variables were selected based on significant single nucleotide polymorphisms associated with each phenotype. We assessed instrumental variable strength, examined confounding factors, and employed inverse variance weighting, weighted median, and MR-Egger approaches for analysis. Results Our analysis included 85 single nucleotide polymorphisms for female infertility and 62 single nucleotide polymorphisms for psychiatric disorders. Results suggest a potential causal relationship between depression and female infertility, with both inverse variance weighting and weighted median methods showing increased infertility risk in depressed patients. Evidence is weak regarding bipolar disorder not increasing female infertility risk. We found no evidence supporting causal links between anxiety, eating disorders, and female infertility. Similarly, no causal relationship was found between female infertility and psychiatric disorders in the opposite direction. Sensitivity analyses and tests for heterogeneity and polymorphism supported result robustness. Conclusions This analysis provides evidence for a potential causal relationship between depression and female infertility. Addressing depression in infertile women may improve fertility outcomes. Further research is needed to explore underlying mechanisms and potential interventions for improving fertility outcomes in women with psychiatric disorders.